Sexual behaviours of the secondary school youths vs. sexual morality system - Kościołek, Aneta; Cuber, Tomasz; Girzelska, Joanna (Polish Journal of Public Health, 2011)
Introduction. Young people who just go into the adult lives face the dilemma of choosing of definite sexual behaviours. The models of sexual behaviours are mostly developed by the identification patterns and undertaken roles of gender, early children’s emotional training, training of social behaviour as well as religious belief and moral principles. Human sexuality can be treated as the mirror where problems of epochs, culture, philosophy and morality are reflected. Sexuality includes biological and anthropological spheres of humanity: inspires questions about personal identity and spiritual and corporeal nature of man, concerns interpersonal relations and commonality structure. Aim. The aim of the study was to reveal the sexual behaviour of the secondary school youths and the way it influences their sexual morality system. Material and methods. The study was conducted on the basis of using diagnostic survey method with application of self-constructed questionnaire. One hundred forty five (145) pupils of the secondary schools from two Polish regions: Mazowieckie and Silesian voivodships took part in the study. The data were collected in January 2010 and statistically and descriptively analysed. Results and conclusions. The study allowed to get knowledge about sexual behaviours and problems of sexual lives of young adult people from Mazowieckie and Silesian voivodships. The average age of respondents was 18 (±1.8). The empirical data show that 52% of pupils already had their sexual initiation. The average age of sexual initiation was 16.5 (±1.5) which confirms the fact of lowering of the age of sexual initiation. This phenomenon sometimes favours the sexual relations with many different partners. Among the sexually active respondents almost 80% used contraceptives to protect against pregnancy. Condom was the most common contraceptive method among young people who took part in the study. Together with the intellectual development of pupils the frequency of using different contraceptive methods grows. Sixty percent of respondents claimed that love was the main factor with decision-making of having sexual intercourses.